Analysis of the Interaction of Saponified Sunflower Oil Surfactant in Potato Starch Biodegradable Films (Solanum tuberosum) - Lucas Perdigão Soares; José Gustavo Lima de Almeida; Edna Maria Mendes Aroucha; Ricardo Henrique de Lima Leite; Rosangela de Carvalho Balaban; Francisco Klebson Gomes dos Santos (Materials Research)
The gradual replacement of petrochemical derivatives with sustainable alternatives is fundamental to reducing environmental impact. Biopolymers such as potato starch stand out for their low cost, biodegradability and sustainability, however, they exhibit hydrophilic properties, leading to poor water resistance and necessitating modifications for improved performance. This study investigated the use of the anionic surfactant saponified sunflower oil (SSO) in the formulation of potato starch films, evaluating its effects on the polymer network and film properties. The films were prepared using the casting method with different dosages of SSO (0.01 g, 0.02 g, 0.04 g, 0.06 g and 0.08 g). Properties such as water vapor permeability (WVP), mechanical behavior, and optical characteristics were analyzed. Micelle formation in the polymer matrix generated vacancies, increasing WVP. At low concentrations, there was a reduction of up to 47.82% in WVP, attributed to the interaction of polar groups in the biopolymer with surfactant monomers, without compromising optical properties. Mechanical properties, such as tensile strength and elasticity, improved at micellar concentrations, to 22.80 MPa and 62.16% respectively. Moreover, this study suggests that the use of additional lipophilic agents may be avoided, reducing costs and broadening post-harvest preservation applications as fruit coatings that extend shelf life.